2015
DOI: 10.1523/jneurosci.1415-15.2015
|View full text |Cite
|
Sign up to set email alerts
|

A Critical Gating Switch at a Modulatory Site in Neuronal Kir3 Channels

Abstract: Inwardly rectifying potassium channels enforce tight control of resting membrane potential in excitable cells. The Kir3.2 channel, a member of the Kir3 subfamily of G-protein-activated potassium channels (GIRKs), plays several roles in the nervous system, including key responsibility in the GABA B pathway of inhibition, in pain perception pathways via opioid receptors, and is also involved in alcoholism. PKC phosphorylation acts on the channel to reduce activity, yet the mechanism is incompletely understood. U… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
16
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 28 publications
(17 reference statements)
3
16
0
Order By: Relevance
“…We next analyzed the rates of current depletion and recovery after Dr-Vsp activation by fitting the decay of current with a single exponential and determining the time constant (tau). These rates correlate with the differences in PIP 2 affinity, where higher-affinity channels typically have a slow depletion and fast recovery ( Bodhinathan and Slesinger, 2013 ; Adney et al, 2015 ; Rjasanow et al, 2015 ). The rate of recovery depends on both the relative affinity of the channel for PIP 2 and the rate of resynthesizing membrane-bound PIP 2 .…”
Section: Resultsmentioning
confidence: 96%
See 1 more Smart Citation
“…We next analyzed the rates of current depletion and recovery after Dr-Vsp activation by fitting the decay of current with a single exponential and determining the time constant (tau). These rates correlate with the differences in PIP 2 affinity, where higher-affinity channels typically have a slow depletion and fast recovery ( Bodhinathan and Slesinger, 2013 ; Adney et al, 2015 ; Rjasanow et al, 2015 ). The rate of recovery depends on both the relative affinity of the channel for PIP 2 and the rate of resynthesizing membrane-bound PIP 2 .…”
Section: Resultsmentioning
confidence: 96%
“…To probe for possible changes in the relative association of PIP 2 with the channel, we studied the effect of reversibly depleting plasma membrane PIP 2 on whole-cell Kir currents using the voltage-activated phosphatase Dr-VSP ( Bodhinathan and Slesinger, 2013 ; Adney et al, 2015 ; Rjasanow et al, 2015 ). Previous studies showed that activation of Dr-Vsp by depolarizing the membrane to +100 mV for varying lengths of time produces a time-dependent, graded depletion of PIP 2 and a corresponding reduction in Kir current ( Bodhinathan and Slesinger, 2013 ).…”
Section: Resultsmentioning
confidence: 99%
“…2 Interactions --A common feature of Kir channels is that they all require the membrane phospholipid phosphatidylinositol (4,5)-bisphosphate (PIP 2 ) to maintain their activity (29). The strength of Kir-PIP 2 interactions determines the sensitivity of Kir channels to several regulatory factors such as pH, protein kinase C, and G proteins (30,31). Kir2.1 channels, with the highest apparent affinity to PIP 2 among the channels tested, was unaffected by NaHS treatment, suggesting that the extent of NaHS effect may depend on the strength of channel-PIP 2 interactions.…”
Section: Inhibition Of Other Kir3 and Kir2 Channels But Activation Ofmentioning
confidence: 99%
“…First, Kir3.2* was expressed and purified from Pichia pastoris as described previously (30). We also purchased from Sigma-Aldrich recombinant Glyceraldehyde 3-phosphate dehydrogenase (GAPDH) purified from Escherichia coli.…”
Section: Kir32 Surface Localization Assay In Xenopus Oocytes --Oocytmentioning
confidence: 99%
“…In the LC, the enhancement of opioid-mediated desensitization appears to be specifically due to PKCa (Bailey et al, 2009a,b). PKC can also reduce GIRK activity directly (Stevens et al, 1999;Mao et al, 2004;Adney et al, 2015). The KF highly expresses PKCg (Lein et al, 2007), which could mediate the heterologous reduction in GIRK current after PDBu, but does not enhance opioid-mediated desensitization.…”
Section: Discussionmentioning
confidence: 99%